THE INFLUENCE OF LEADERSHIP AND WORK DISCIPLINE ON VILLAGE APPARATUS PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE IN SEMPU DISTRIC - Edi Santoso; Rr. Hermien Tridayanti (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of leadership and work discipline on the performance of village officials, with work motivation as the intervening variable in Sempu District. This study used a quantitative approach with path analysis techniques. The population in this study was all village officials in seven villages within Sempu District. The results indicate that leadership and work discipline have a significant influence on work motivation and performance. Furthermore, work motivation proved to be an intervening variable, strengthening the relationship between the independent variables and official performance. These findings suggest that improving the quality of leadership and work discipline can encourage more optimal performance of village officials.